THE ROLE OF TIKTOK LIVE STREAMING IN BUILDING INTERACTIVE COMMUNICATION WITH CONSUMERS: A CASE STUDY OF THE @JUNE_COLLECTIONS ACCOUNT - Santa Carolina Sagala; RR. Roosita Cindrakasih (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This study examines the role of TikTok's live streaming feature in building interactive communication between the @june_collections account and consumers of children’s clothing aged 0-6 years. Using a qualitative approach with a case study design, the research involved five purposively selected informants comprising the business owner, the main host, and three active consumers. Data were collected through in-depth interviews, non-participant observation of eight live streaming sessions, and account documentation. Data were analyzed using the Miles, Huberman, and Saldaña (2014) interactive model and validated through expert triangulation. Findings indicate that live streaming operates as a multidimensional communication medium through three primary functions: bridging information gaps, transforming transactional into relational interactions, and cultivating a loyal consumer community. The three most dominant interactive communication elements are personalization, responsiveness, and entertainment. Communication strategies employed include a non-coercive approach, sensory-rich product demonstrations, organic testimonials as social proof, and the simultaneous integration of the 4P marketing mix in each broadcast session. This study affirms that live streaming commerce, implemented with an appropriate communication strategy, serves as a sustainable relationship-building medium between small businesses and their consumers.